SAT0377 DIFFERENCES IN CLINICAL CHARACTERISTICS, QUALITY OF LIFE, DISABILITY, AND WORK PRODUCTIVITY IN PSORIATIC ARTHRITIS PATIENTS BY GENDER: FINDINGS FROM A CROSS-SECTIONAL SURVEY IN THE US AND EUROPE. (June 2019) - Gossec, Laure; Walsh, Jessica A.; Michaud, Kaleb; Peterson, Steve; Holdsworth, Elizabeth; Karyekar, Chetan; Booth, Nicola; Kemp, Jessalyn; Chakravarty, Soumya D.; Kafka, Shelly; Ogdie, Alexis
Abstract : Background: Psoriatic arthritis (PsA) prevalence is equal in men and women, though gender may play a role in driving mechanisms of PsA leading to differences in manifestations of clinical disease (1). Objectives: Assess key differences in clinical characteristics, disability, quality of life, and work productivity by gender in real-world practice. Methods: Cross-sectional survey of rheumatologists and dermatologists and their patients in France, Germany, Italy, Spain, UK, and US. Data were collected from Jun-Aug 2018 via physician-completed patient record forms and patient self-completed forms. Data were analyzed by gender. Demographic characteristics, treatment use, and clinical characteristics (Tender Joint Count [TJC], Swollen Joint Count [SJC], Body Surface Area [BSA] psoriasis) were reported by physicians, while quality of life (EQ5D and PsAID12), disability (HAQ-DI), and work productivity (WPAI) were reported by patients. Men and women were compared using parametric tests and non-parametric tests where appropriate. Results: Data were collected for 2270 patients (595 US, 1675 Europe). Demographic characteristics, time from first symptoms to diagnosis, biologic treatment, and clinical characteristics were comparable between women and men (Table 1 ). More women reported worse quality of life, disability, and work activity impairment than men (Table 2 ). Conclusion: In women and men with similar PsA disease activity and treatment rates, women experienced worse quality of life, greater disability, and greater work impairment, despite a lower burden of comorbidities. Reference: [1] Billi AC, Kahlenberg JM, Gudjonsson JE. Sex bias in autoimmunity. Curr Opin Rheumatol. 2019 Jan;31(1):53–61. Disclosure of Interests: Laure Gossec Grant/research support from: AbbVie, BMS, Celgene, Janssen, Lilly, MSD, Novartis-Sandoz, Pfizer, Sanofi, and UCB, Consultant for: AbbVie, Biogen, BMS, Celgene, Janssen, Lilly, MSD, Nordic Pharma, Novartis-Sandoz, Pfizer, Roche, Sanofi, and UCB, Consultant for: L Gossec has received honoraria from Celgene as investigator for this study, Jessica A. Walsh Grant/research support from: Abbvie, Pfizer, Consultant for: Abbvie, Celgene, Lilly, Novartis, Kaleb Michaud Grant/research support from: Pfizer (within past 2 years), Steve Peterson Shareholder of: Janssen, Employee of: BMS (2000-2002), Janssen (2002-present), Elizabeth Holdsworth Employee of: Adelphi Real World, Chetan Karyekar Shareholder of: J&J, Employee of: Janssen Scientific Affairs, LLC, Abbott, BMS, Novartis, Nicola Booth Employee of: Adelphi Real World, Jessalyn Kemp Employee of: Adelphi Real World, Soumya D Chakravarty Shareholder of: Johnson & Johnson, Employee of: Johnson & Johnson, Shelly Kafka Shareholder of: J&J, Employee of: J&J, Alexis Ogdie Grant/research support from: (To my university) Novartis, Pfizer, Grant/research support from: Novartis, Pfizer, Grant/research support from: Novartis, Pfizer, Grant/research support from: Novartis, Pfizer, Consultant for: AbbVie, Bristol-Myers Squibb, Celgene, Corrona, Eli Lilly and Company, Novartis, Pfizer, and Takeda, Consultant for: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Corrona, Eli Lilly, Novartis, Pfizer Inc, Takeda, Consultant for: Abbvie, Amgen, BMS, Celgene, Corrona, Lilly, Novartis, Pfizer, Takeda, Consultant for: Abbvie, Amgen, BMS, Celgene, Corrona, Lilly, Novartis, Pfizer, Takeda